2021
DOI: 10.1155/2021/6610543
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Oroxylin A against Doxorubicin‐Induced Cardiotoxicity via the Activation of Sirt1 in Mice

Abstract: Doxorubicin- (DOX-) related cardiac injury impairs the life quality of patients with cancer. This largely limited the clinical use of DOX. It is of great significance to find a novel strategy to reduce DOX-related cardiac injury. Oroxylin A (OA) has been identified to exert beneficial effects against inflammatory diseases and cancers. Here, we investigated whether OA could attenuate DOX-induced acute cardiotoxicity in mice. A single dose of DOX was used to induce acute cardiac injury in mice. To explore the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Previous studies have revealed that Sirt1 was decreased in DOX treated heart or H9c2 cardiac cells ( Zhang S. et al, 2021 ; Liu Y. et al, 2021 ; Zhang WB. et al, 2021 ), and PI3K-Akt-GSK3β signaling pathway is required for Sirt1 induction by endoplasmic reticulum stress ( Koga et al, 2015 ), we then tested the protein expression of Sirt1.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies have revealed that Sirt1 was decreased in DOX treated heart or H9c2 cardiac cells ( Zhang S. et al, 2021 ; Liu Y. et al, 2021 ; Zhang WB. et al, 2021 ), and PI3K-Akt-GSK3β signaling pathway is required for Sirt1 induction by endoplasmic reticulum stress ( Koga et al, 2015 ), we then tested the protein expression of Sirt1.…”
Section: Resultsmentioning
confidence: 94%
“…The authors linked the protective effects exerted by OA administration to preserved levels of expression of sirtuin 1 (Sirt1), a critical deacetylase that is downregulated by DOX. They reported that OA is not protective in cardiac-restricted Sirt1 KO mice, showing that OA relies on Sirt1 activity to prevent acute DOX-induced cardiotoxicity [ 11 ].…”
mentioning
confidence: 99%
“…Previous literatures have shown that oroxylin A inhibits inflammation by influencing the activity of many molecules (NLRP3 inflammasome, ERK, PI3K/AKT, Nrf2/ARE, NF-κB, etc.) ( Yao et al, 2014 ; Ye et al, 2014 ; Zhou et al, 2017 ; Zhang et al, 2021a ). Previous literatures have also indicated that oroxylin A not only inhibits H 2 O 2 -induced oxidative stress in PC12 cells but also prevents doxorubicin-induced cardiotoxicity by activating sirt1 in mice ( Han et al, 2017 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Yao et al, 2014 ; Ye et al, 2014 ; Zhou et al, 2017 ; Zhang et al, 2021a ). Previous literatures have also indicated that oroxylin A not only inhibits H 2 O 2 -induced oxidative stress in PC12 cells but also prevents doxorubicin-induced cardiotoxicity by activating sirt1 in mice ( Han et al, 2017 ; Zhang et al, 2021 ). It should be noticed that the pathogenesis of depression is accompanied with neuroinflammation, neuronal oxidative stress and sirt1 dysfunction ( Lu et al, 2018 ; Bhatt et al, 2020 ; Troubat et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%